2001
DOI: 10.1016/s0885-3924(01)00313-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Symptom Palliation for Patients Attending a Rapid Response Radiotherapy Program

Abstract: Clinical trials generally include motivated patients with relatively good performance status. This can result in an overestimation of the effectiveness of an intervention. Clinic follow-up protocols for outcome assessment after palliative treatments suffer from high attrition rates. In this study, the feasibility of telephone follow-up for the assessment of symptom palliation in patients receiving outpatient palliative radiotherapy as a tool to evaluate outcome was examined. Patients referred for palliative ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 19 publications
1
37
1
1
Order By: Relevance
“…More than 130 relevant articles and abstracts were identified, of which thirty-nine were primary studies published as complete peer-reviewed papers, representing 25 different institutions. Of the thirty-nine papers, thirteen were from Canada 6,11,[20][21][22][23][24][25][26][27][28][29][30] ; eight were from the United States [12][13][14]18,[31][32][33][34] ; eight were from Scandinavia (Sweden 15,[35][36][37] , Denmark [38][39] , Norway 40 , Finland 16 ); two were from Western Europe (Netherlands 41 , United Kingdom 42 ); five were from southern Europe (Switzerland 43 , Italy 17,[44][45][46] ); two were from Australia 47,48 ; and one was from Asia 49 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 130 relevant articles and abstracts were identified, of which thirty-nine were primary studies published as complete peer-reviewed papers, representing 25 different institutions. Of the thirty-nine papers, thirteen were from Canada 6,11,[20][21][22][23][24][25][26][27][28][29][30] ; eight were from the United States [12][13][14]18,[31][32][33][34] ; eight were from Scandinavia (Sweden 15,[35][36][37] , Denmark [38][39] , Norway 40 , Finland 16 ); two were from Western Europe (Netherlands 41 , United Kingdom 42 ); five were from southern Europe (Switzerland 43 , Italy 17,[44][45][46] ); two were from Australia 47,48 ; and one was from Asia 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Sample sizes in the thirty-three oncologic studies ranged from 32 to 1296 subjects, for a total in excess of 5000 patients. However, eleven of the thirty-three studies reported some data for the same patients: Sunnybrook Cancer Centre in Canada [25][26][27][28] , Bispebjerg Hospital in Denmark [38][39] , Linkoping Hospital in Sweden 15,35,36 , and Yale University 18,34 . For the patients described in the thirty-three papers, median age ranged from 53 to 74 years, and men were in a slight majority overall.…”
Section: Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wait time of 7 days is recommended in patients with aggressive tumours and in some palliative patients 6 . Unfortunately, the delivery of timely palliative radiation therapy to patients in Ontario continues to be an issue of concern because of limitations in resources, equipment, and personnel 7 . And prolonged wait times are not an issue confined to Ontario; countries including England and Australia are dealing with the same problem 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary RRPC have shown to expedite patient's palliative radiotherapy both nationally and internationally 2, 9, 10. An assessment of the established RRPC at ROMC in 2005, showed patients referred to the RRPC waited less time to receive palliative radiotherapy compared with patients seen outside the RRPC 2.…”
Section: Introductionmentioning
confidence: 99%